Kooperative Ausbildung im technischen Lehramt Kompetenzorientierte Lehrerbildung für berufsbildende Schulen im gewerbl.-techn. Bereich - Niethammer, Manuela; Hartmann, Martin D. (W. Bertelsmann Verlag, 2015)
A new training concept for teaching at vocational schools was developed, tested and analysed at TU Dresden. The innovative study model combines academic and vocational training. The publication introduces the model, the findings of the accompanying scientific study and recommendations for a practise-oriented teacher training for vocational schools. The cooperative study course brings together traditional studies with professional practice. Students have the option of obtaining a skilled worker certification in this course of study. 71 companies, four education providers and 66 students took part in the model project "Cooperative training for technical teaching" (Kooperative Ausbildung im technischen Lehramt - KAtLA), which was financed by the European Social Fund.
Description based on print version record.
KU Open Services
Keywords: Social Science / Sociology; Social sciences; Electronic books